STUDI MENGENAI DINAMIKA HIDUP KELUARGA MUDA KRISTIANI YANG MEMILIKI TANTANGAN JARAK DAN WAKTU, SERTA PELUANGNYA BAGI PASTORAL KELUARGA - Nathalia Dwi Oetari; Albert I Ketut Deni Wijaya (Bahasa Indonesia, 2017)
God has created man in pairs. God presents a friend worthy of human life and gives it to him. God does not let man himself. Man is God's partner in managing the universe and everything in it. The sacrament of marriage is a sign and means derived from God that is useful to unite men and women to become married couples. Choosing to become a husband and wife is a call and a very noble lifestyle for everyone. Family life makes men and women united through the bonds of the sacrament of marriage. The sacred promise of marriage is the goal of happy and eternal marriage for catholic families that must be manifested in mutual respect, mutual love, mutual acceptance of each other, loving, honest, open, trusting and always grateful. The development of this era, threaten the survival ofthe family. The development of this era cannot be separated from the flow of globalization, where the family also responds to the flow of globalization that can attract every member of the family has an attitude of individualism, materialism, consumerism, and hedonism. It is also experienced by catholic families, especially young families who are trying to build a prosperous family. Welfare is championed even to have to work in another city leaving family members, this decision ultimately young families have the challenge of distance and time. The young Christian families who has the challenge of distance and time is a Christian family built over a period of 1 to 5 years apart distance and time with family members. This research uses a qualitative approach. The respondents of this study were Christian families built over a period of 1 to 5 years apart from time and distance with family members residing in the parish of St. Cornelius and parish Mater Dei, Madiun. The number of respondents are 7 young Christian families. Based on the results of the study, young Christian families with the challenges of distance and time experienced difficulties and impacts on three things: limited time shared by family, lack of father or mother figure, and relationship between parent and child. The pastoral opportunities for pastoral workers can do are emphasizing the pastoral function of guiding and nurturing.